2020
DOI: 10.3389/fonc.2020.532285
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Limitations of Cisplatin Therapy by Additional Treatment With the HSP90 Inhibitor Onalespib

Abstract: Rational: Cisplatin based cancer therapy is an affordable and effective standard therapy for several solid cancers, including lung, ovarian and head and neck cancers. However, the clinical use of cisplatin is routinely limited by the development of drug resistance and subsequent therapeutic failure. Therefore, methods of circumventing cisplatin resistance have the potential to increase therapeutic efficiency and dramatically increase overall survival. Cisplatin resistance can be mediated by alterations to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Interestingly, recent study suggested that the mechanism of HSP90-mediated resistance could be not only limited to above pathway, but also be involved in the upregulating DNA repair pathways. This is confirmed by the results revealing that Hsp90 inhibitor could cause suppression of DNA repair mechanisms to enhance drugmediated DNA damage in cisplatin-resistant cancer cells, and finally reversed the resistance phenotype (81).…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, recent study suggested that the mechanism of HSP90-mediated resistance could be not only limited to above pathway, but also be involved in the upregulating DNA repair pathways. This is confirmed by the results revealing that Hsp90 inhibitor could cause suppression of DNA repair mechanisms to enhance drugmediated DNA damage in cisplatin-resistant cancer cells, and finally reversed the resistance phenotype (81).…”
Section: Discussionsupporting
confidence: 56%
“…Subsequent to this report, another publication has drawn similar conclusions for the combination of AT13387 with cisplatin, another DNA-damaging agent [ 13 ]. The therapeutic potential of utilizing Hsp90 inhibitors most effectively yet remains to be realized.…”
Section: Combination Study With At13387 and Radiationmentioning
confidence: 58%
“…However, the lack of increased DNA damage for 17AAG alone and the combination treatment in DB could be explained by the most synergistic concentration being four times lower than in RIVA and OCI-Ly7. In agreement, the combination of cisplatin and an Hsp90 inhibitor has been shown to decrease cell viability and induce DNA damage response in ovarian and head and neck cancer cells [23][24][25].…”
Section: Discussionmentioning
confidence: 87%